COMPARATIVE ANALYSIS GOVERNMENT REGULATION NUMBER 23 OF 2018 WITH GOVERNMENT REGULATION NUMBER 55 OF 2022 IN TERMS OF MSMEs TAX ARRANGEMENTS - Afkarini, Izzah; Nurdiannova, Arief (Sekolah tinggi ilmu ekonomi pemuda, 2024)
This research aims to analyze the comparison between Government Regulation number 23 of 2018 and Government Regulation number 55 of 2022. In this research, it is explained about changes in the MSMEs tax rate, which in Government Regulation number 23 of 2018 is explained for taxpayers who have gross turnover below Rp. 4.8 billion in a year with a tax rate of 0.5%, but if the individual MSMEs tax has an annual turnover of not more than Rp. 500 million, then it will not be subject to final income tax on MSMEs Government Regulation number 55 of 2022, as explained in government regulation number 55 of 2022, it is explained that individual and corporate taxpayers who have business turnover below Rp. 500,000,000 will not be subject to final income tax 0.5%, however if the taxpayer has a business above Rp . 500,000,000-RP. 4.8 billion in one tax year will be subject to a tax rate of 0.5%. The aim of the research with the title